A Case for Doxycycline as an Effective Treatment for Confluent and Reticulated Papillomatosis (CARP) - Aishwarya Sharma; Deborah Moon; Dong Joo Kim (Case Reports in Dermatological Medicine)
Confluent and reticulated papillomatosis (CARP) is a rare keratinization disorder that presents with asymptomatic, reticulated papules coalescing into plaques, which adversely affect, most often, young black persons. Minocycline is considered the drug of choice, but it is not without its host of potential side effects, including drug hypersensitivity, drug-induced lupus/vasculitis/hepatitis, blue-gray skin hyperpigmentation, acute eosinophilic pneumonia, pseudotumor cerebri, and vestibular instability, among others. Alternatively, doxycycline might be considered as another first-line agent for CARP as it can effectively clear lesions while offering a more favorable side effect profile in select patients. Herein, we present a case of CARP successfully resolved with doxycycline after a protracted treatment history of topical and oral antifungal medications for suspected tinea versicolor (TV).